- #1

- 594

- 12

## Homework Statement

Use Snell's law to show fresnel Eq 1 can be expressed as Eq 2

Eq 1 = (ncosθ-n'cosθ') / (ncosθ+n'cosθ)

Eq 2 = (tanθ' - tanθ) / (tanθ' + tanθ)

## Homework Equations

nsinθ=n'sinθ' (Snell's law)

## The Attempt at a Solution

n' = nsinθ / sinθ'

Substitute n' into equation and then multiply numerator and denominator by sinθ'/n gives:

(cosθsinθ'-cosθ'sinθ) / (cosθsinθ'+cosθ'sinθ)

I'm not sure how to get from here to Eq 2 though. I know sinθ/cosθ = tanθ and cosθ/sinθ=1/tanθ.